TINJAUAN HUKUM ISLAM TERHADAP PRAKTEK ARISAN BERANAK (Studi Kasus Desa Sidorejo Kecamatan Wonomulyo) - Ratna Sari; Muhammad Nuzur (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2021)
The focus of the problem of this research is how the practice of arisan with children in the form of money is added in Sidorejo Village, Wonomulyo District and how Islamic law reviews the practice of arisan with children required in each lottery in Sidorejo Village, Wonomulyo District. This type of research is classified as a descriptive qualitative where researchers who go directly to the research location. The approach used in the research is the syar'i approach and the social approach. While the data sources of this research are primary and secondary data sources. Data processing techniques in this study include observation, interviews and documentation. The research instrument is the researcher himself. Testing the validity of the data in this study using trigulation. The results of this study indicate that the practice of social gathering for children in Sidorejo Village, Wonomulyo District uses debt-receivable contracts. Those who are lucky and those who are in debt, namely those who get the arisan lottery early are the debtors (creditors) because they have to pay the deposit and additional monthly payments to those who have not received it. And those who have debts (debtors) are members who get the arisan later because they provide loans to members who get the lottery first. The view of Islamic law on the addition in the practice of arisan for children is the same as usury in debts. Because there are additions that have been agreed upon at the beginning of the arisan, the additions increase little by little every month. The implications of the research are good if there is an addition to the practice of this social gathering using a mudharabah contract. Each member gets a share of the profits of the job that gets the lottery first. Only providing a small addition if the basic ingredients increase so as not to burden the arisan actors with additional items that continue to increase every month.Keywords: Islamic Law, Arisan Beranak.